2013
DOI: 10.3892/etm.2013.1134
|View full text |Cite
|
Sign up to set email alerts
|

Carbamylated erythropoietin attenuates cardiomyopathy via PI3K/Akt activation in rats with diabetic cardiomyopathy

Abstract: The aim of the present study was to investigate the protective effect of carbamylated erythropoietin (CEPO) against cardiomyopathy in high-fat, high-carbohydrate diet-fed rats with streptozotocin (STZ)-induced diabetic cardiomyopathy (DCM). Healthy male Wistar rats were fed a high-fat, high-carbohydrate diet for four weeks, and then were injected with STZ twice (50 mg/kg, intraperitoneally). Once DCM was confirmed, the rats were divided randomly into the following groups: DCM without treatment, CEPO treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 37 publications
(46 reference statements)
3
7
0
2
Order By: Relevance
“…For example, Wu et al 43 suggested that resveratrol exerted a protective effect on neonatal rats with DCM by inhibiting myocyte apoptosis through the PI3K/Akt/FoxO3a signal transduction pathway. Similarly, He et al 44 pointed out that carbamylated erythropoietin is capable of attenuating cardiomyopathy by activating the PI3K/Akt signal transduction pathway in rat models of DCM. Recently, it has been reported that the PI3K/Akt signal transduction pathway played a significant role in the regulation of cardiocyte metabolism.…”
Section: Discussionmentioning
confidence: 93%
“…For example, Wu et al 43 suggested that resveratrol exerted a protective effect on neonatal rats with DCM by inhibiting myocyte apoptosis through the PI3K/Akt/FoxO3a signal transduction pathway. Similarly, He et al 44 pointed out that carbamylated erythropoietin is capable of attenuating cardiomyopathy by activating the PI3K/Akt signal transduction pathway in rat models of DCM. Recently, it has been reported that the PI3K/Akt signal transduction pathway played a significant role in the regulation of cardiocyte metabolism.…”
Section: Discussionmentioning
confidence: 93%
“…Results of western blotting assay showed that CEPO could elevate the level of pAkt, which was inhibited by treatment of LY, suggesting that CEPO can ameliorate the heart function of CHF rats through PI3-K/Akt signal pathway. Results in this study agreed with those of He et al ( 23 ).…”
Section: Discussionsupporting
confidence: 94%
“…Nevertheless, the present study showed that CEPO significantly downregulated the CC3 expression at similar time points compared to the I/R group. The effect of CEPO on CC3 was similar to the findings of previous studies using different animal models [27, 28]. These findings suggest that CEPO might sufficiently provide early beneficial effects for intrauterine HIE.…”
Section: Discussionsupporting
confidence: 88%